Exploring the changes in the field of HRM - Hua, Weiwei (2007)
Human resource management (HRM) involves the administration of employees to achieve managers' objectives. It is different from traditional resource management that originated in the USA and have adopted in the UK. However, according to Frege's (2005) study, the academic interests outside the UK and US, and the increase of global academic cooperation (e.g. joint publications by authors from different national institutions, international conferences), there are some changes of HRM issues in the 21st century compared with that in the early 1990s. Hence, the objective of this dissertation is to explore the main changes in the field of HRM focusing on the research patterns and content of topics. Also, it aims to examine the recent tendency of HRM research towards internationalization.